Tracking the Selective Pressure Profile and Gene Flow of SARS-CoV-2 Delta Variant in Italy from April to October 2021 and Frequencies of Key Mutations from Three Representative Italian Regions - Alessandra Lo Presti; Angela Di Martino; Luigina Ambrosio; Luca De Sabato; Arnold Knijn; Gabriele Vaccari; Ilaria Di Bartolo; Stefano Morabito; Calogero Terregino; Alice Fusaro; Isabella Monne; Edoardo Giussani; et al. (Microorganisms, 2023)
The SARS-CoV-2 Delta variant of concern (VOC) was often associated with serious clinical course of the COVID-19 disease. Herein, we investigated the selective pressure, gene flow and evaluation on the frequencies of mutations causing amino acid substitutions in the Delta variant in three Italian regions. A total of 1500 SARS-CoV-2 Delta genomes, collected in Italy from April to October 2021 were investigated, including a subset of 596 from three Italian regions. The selective pressure and the frequency of amino acid substitutions and the prediction of their possible impact on the stability of the proteins were investigated. Delta variant dataset, in this study, identified 68 sites under positive selection: 16 in the spike (23.5%), 11 in nsp2 (16.2%) and 10 in nsp12 (14.7%) genes. Three of the positive sites in the spike were located in the receptor-binding domain (RBD). In Delta genomes from the three regions, 6 changes were identified as very common (>83.7%), 4 as common (>64.0%), 21 at low frequency (2.1%–25.0%) and 29 rare (≤2.0%). The detection of positive selection on key mutations may represent a model to identify recurrent signature mutations of the virus.